PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V.A SD NEGERI 37 PEKANBARU - Nora Efmawati; Syahrilfuddin '; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research is motivated student learning outcomes VA Elementary School Grade 37 Pekanbaru is still far from the minimum completeness criteria (KKM) that has been set in the school is 75, in which the from the 38 people, only 19 students or 50% were reached KKM the school hafassigned. Whereas 19 students or 50% geting scored below the KKM, with an average value of 66.45 class. The purpose of this research is to improve student learning outcomes IPA Grade Elementary School VA 37 Pekanbaru with the implementation of Cooperative Learning and Student Team Achievement Division (STAD) mode. Subjects in this study were students of class VA SD Negeri 37 Pekanbaru, the number of students 38 people, consisting of 14 students sex male and 24 female students. This research was conducted in two cycles, where each cycle consisted of three meetings. The first and second meetings to explain the learning material. Then at the third meeting at the end of the cycle is a replay. From the results of this study concluded that the mode of type STAD cooperative learning can improve learning outcomes VA grade science students of SD Negeri 37 Pekanbaru, it can be seen from several things, namely: (1) Increased activity of teachers and students. At the first meeting of the first cycle of teacher activity only 54.17%. Then in the second meeting of the first cycle increased by 66.67%. At the third meeting of the second cycle is also increased to 83.33% and the fourth meeting of the second cycle increased to 95.83%. While the activities of students at the first meeting of the first cycle of only 45.83%. Then in the second meeting of the first cycle increased to 58.33%. At the third meeting of the second cycle of observation of student activity increased to 75% and in the fourth meeting of the second cycle increased to 91.67%. (2) Improved student learning outcomes, where the base score is the average value obtained by the students only 66.45. Then in the first cycle of the average value obtained by students increased to 81.45, and in the second cycle increased to 86.32. In addition, improving student learning outcomes can also be known from mastery learning outcomes of students individually and classical, where the base score of students who pass are only 19 people with 50% percentage, in the first cycle of repetition increased to 28 people with 73.67% percentage, and the repeat second cycle increased to 36 students with 94.74% percentage.Keywords: Cooperative Learning Model STAD, IPA Learning Outcomes2